PENGARUH PENERAPAN GREEN ACCOUNTING TERHADAP KINERJA PERUSAHAAN - Santika, Yenti (Universitas Nusantara PGRI Kediri, 2023)
Environmental issues are currently a social being highlighted by the community. Many environmental damage cases have occurred in Indonesia. It shows that the company's attention to the environment is still relatively low. The implementation of green accounting will minimize environmental issues. This study aims to analyze the effect of environmental performance, environmental disclosure, and environmental costs on company performance. This quantitative research uses secondary data in annual and sustainability reports. The population of this research is companies in basic material, energy, and consumer non-cyclicals sector that listed in Indonesia Stock Exchange (IDX) for 2020 and 2021 periods. There were 49 samples obtained by purposive sampling. The data were processed using multiple linear regression models. The results showed that environmental costs had a significant positive effect on company performance. However, environmental performance and environmental disclosure had no effect on company performance.